De fiere nachtegaal Het Nederlandse lied in de middeleeuwen - Grijp, Louis Peter; Willaert, Frank (Amsterdam University Press, 2008)
The Proud Nightingale covers the many facets of medieval music in the Netherlands until the year 1600. Eighteen authors discuss songs ranging from of courtly songs, including minstrels, mystics and Modern Devots, on the performance and the oral tradition of ancient songs, and on intertextuality. What is new is the use of ethnological perspective by a number of the authors. This book is a collection of songs: messages from loved ones to joyous songs sung by groups at home and in the pub, or by farmers and servants whilst weeding, mowing and harvesting. At the same time religious melodies convey their desire for God or their distaste of the world.